FINANCIAL SUPPORT FOR THE DEVELOPMENT OF LOCAL COMMUNITIES IN DEVELOPED COUNTRIES: IMPLEMENTATION IN DOMESTIC PRACTICE (INNOVATIVE ECONOMY, 2025)
Uhryn A.P.  FINANCIAL SUPPORT FOR THE DEVELOPMENT OF LOCAL COMMUNITIES IN DEVELOPED COUNTRIES: IMPLEMENTATION IN DOMESTIC PRACTICEPurpose. The aim of the article is to summarise and systematise international experience in financial support for the development of local communities in developed countries and to substantiate the directions for its implementation in domestic practice, taking into account the tasks of strengthening the revenue base of local budgets in Ukraine, increasing the institutional stability of communities and ensuring their sustainable development in the context of post-war recovery and budget decentralization.Methodology of research. The methodological basis of the study is the systemic and institutional approaches, which made it possible to consider local finances as a complex multi-level system in which budgetary, tax, and transfer mechanisms interact within the current institutional environment. In the process of research, comparative analysis methods were used to compare models of local finance organization and mechanisms of fiscal decentralization in different countries, logical generalization to form theoretical conclusions and conceptual provisions, as well as structural and functional analysis to identify the role of individual elements of the budget system in ensuring the financial autonomy of local self-government. Thus, the research methodology is based on a comprehensive combination of modern theoretical and methodological approaches to analysing the functioning of the public finance system in decentralized conditions. The theoretical basis of the work is formed by the provisions of the theory of fiscal federalism, which reveal the patterns of distribution of revenue and expenditure powers between levels of government, the concept of tax autonomy of territorial communities, as well as scientific approaches to inter-budgetary equalization as a tool for ensuring financial capacity and balanced regional development.Findings. It has been established that the effectiveness of financial support for local communities is determined by a balanced combination of tax autonomy, stable own and fixed revenues, as well as effective mechanisms of vertical and horizontal financial equalisation. The institutional features of decentralised, cooperative and centralised models of local finance, their impact on the financial stability of communities and the quality of public services are revealed.It is substantiated that Ukraine's priorities are: strengthening the role of personal income tax and property tax in local budget revenues, improving formula equalisation based on European models, developing municipal investment and project financing instruments, and integrating international aid into the local finance system while maintaining budgetary discipline. The obtained results correspond to the tasks of improving the effectiveness of community’s information and communication resources and strengthening the financial capacity of territories.Originality. International models of financial support for territorial communities have been systematised through the prism of combining tax autonomy and solidarity mechanisms; adaptation guidelines for Ukraine have been substantiated, combining the expansion of communities' own revenue base with the improvement of inter-budgetary relations and the strengthening of the financial responsibility of local self-government bodies.Practical value. The proposed approaches can be used by public authorities and territorial communities of Ukraine to form a sustainable revenue policy, optimise the financial equalisation system, plan development investments and improve the quality of budget management. The research results are relevant to scientific and practical tasks of improving local budget revenue management and introducing strategic risk management into community activities.Key words: financial support for local communities, fiscal decentralization, local budgets, tax autonomy, inter-budgetary relations, financial equalisation, post-war recovery.
Keywords: financial support for local communities; fiscal decentralization; local budgets; tax autonomy; inter-budgetary relations; financial equalisation; post-war recovery